Hérnia interna ocasionada por aderências abdominais em uma mulher de 80 anos: um relato de caso - Bezerra, João Zeca de Jesus (2018)
Internal hernia is a rare condition and It is a difficult diagnosis in the preoperative rating (BRUM BRENNER, 2014). However, it is a differential diagnosis in acute abdomen (BRUNETTI, 2007). In turn, Is a frequent condition in the ready care (POSTIER, 2008). This paper intends to report a case treated in a referral hospital in the Brazilian state of Sergipe. At the same time arguing the approach to the most current evidence on the subject.